Surface Subsidence Control during Deep Backfill Coal Mining: A Case Study - Baiyi Li; Nan Zhou; Wenyue Qi; Ailing Li; Zhizhong Cui (Advances in Civil Engineering)
Deep resource exploitation is imperative, but it is facing with more complicated mining environment and more dangerous mining disturbances to induce the potential catastrophe process. Solid backfill technology, which can control the strata movement and prevent potential hazards, has been used as the primary method in deep mining for surface subsidence control and ecosystem protection. In this study, taking backfill mining area no. 930 in the Tangkou coal mine as background, the probability integral model was adopted to predict the surface subsidence at different mining depths and filling ratios. The filling ratio was designed for deep mining based on the regression analysis of the predicted surface subsidence results. The study shows that the backfilling ratio at the Tangkou deep coal mining area should be controlled at a level greater than 82.5%, and the mining damage to the surface under this condition was analyzed. Furthermore, control strategies for deep backfill mining are proposed in which the backfill density can be enhanced by optimizing the tamping machine, material composition, and tamping process. Finally, the measurement of the backfill mass and surface subsidence showed that the actual filling ratio was controlled at 82.57%, which ensures adequate protection of the surface buildings during the mining process.